ANALISIS PENGARUH ISLAMIC BRANDING DAN E-WOM TERHADAP KEPUTUSAN PEMBELIAN ONLINE KONSUMEN DI GOFOOD : STUDI PADA MAKANAN HALAL ARABIAN FAST FOOD DI KOTA MAKASSAR - Azhari, Azlan (Gapenas Publisher, 2025)
This study aims to analyze the influence of Islamic branding and electronic word of mouth (e-WOM) on purchasing decisions for Arabian fast food through the GoFood application in Makassar City. The background of this study is based on the increasing consumer preference for halal food that is easily accessible digitally, as well as the importance of understanding consumer trust factors such as Islamic branding and the influence of online reviews in the online purchasing decision-making process. This study uses a quantitative approach with multiple linear regression methods to examine the relationship between variables. The population in this study were all active users of the GoFood application in Makassar City who had ordered halal Arabian Fast Food at least once in the last three months since April 2025. The sampling technique used was accidental sampling, with a sample size of 75 respondents. The data collection method was carried out through the distribution of online questionnaires using Google Forms, with a 5-point Likert scale instrument. The data obtained were then analyzed using the SPSS program version 22, which includes validity tests, reliability tests, t-tests, F-tests, and coefficients of determination (R²). The results of the study indicate that the two independent variables, namely Islamic Branding and E-WOM, partially have a positive and significant effect on consumer purchasing decisions. Among the two variables, Islamic Branding has the most dominant influence with a regression coefficient value of 0.561 and a significance value of 0.000. This indicates that elements of Islamic identity such as halal assurance, Islamic symbols, and sharia values ??contained in product branding are the main factors in forming trust and encouraging Muslim consumers to make purchases through GoFood. This finding emphasizes the importance of value-oriented branding strategies and digital reputation management in increasing trust and purchasing decisions in the halal food delivery service ecosystem.